Supplementation of garlic powder and Lactobacillus casei to improve nutrient digestibility, physiological conditions, and performance of broiler during starter phase - Mangisah, I.; Yunianto, V. D.; Sumarsih, S.; Sugiharto, S. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
This study aimed to assess the effect of a mixture of garlic powder and Lactobacillus casei (GLC) on intestinal development, hematological parameters, nutrient digestibility, and performance of broilers in the starter phase. One hundred forty 1-day-old broiler chicks were divided into four groups, namely control (not given GLC supplement) and given GLC supplement either 1%, 2%, and 3% of total feed. Chickens were reared for 21 days in an open cage. On the 21st day of the experiment, blood collection, lymphoid organ and digestive organ weight, and performance data were recorded. Accumulative feed intake until day 21 did not differ (P>0.05) among treatment groups. In this study, there were improvements in the height of villi in the jejunum, and the acidity in the duodenum and caecum, due to the increase of short-chain fatty acids (SCFA: acetate and propionate). Protein and crude fiber digestibility in the GLC-given chickens was significantly higher than in the control group ((P≤0.05). GLC supplementation (1%, 2%, and 3% of total feed) significantly increased body weight gain and improved feed conversion ratio (FCR) (P≤0.05). In conclusion, the use of GLC during the starter phase can improve the nutrient digestibility, intestinal health, and performance of broiler chickens.